THE PERUVIAN TAX SYSTEM AND ITS PENDING RESTRUCTURING - Montes Farro, Eduardo Alberto (2009)
The tax system suffers from several defects in substance and form. We need a comprehensive rethinking, enabling a broad universe of taxpayers, easy understanding, compliance and control. Must be based on clarity, accuracy, fairness and justice.